Effect of renin-angiotensin -aldosterone system blockers on myocardial remodeling processes and risk for atrial fibrillation in patients with arterial hypertension - O. M. Drapkina; M. V. Kostyukevich (Klinicist, 2014)
The given review considers the mechanisms underlying the development and maintenance of atrial fibrillations (AF). It is noted that the processes of atrial fibrosis, ion channel remodeling, inflammation, apoptosis, impaired intercellular interactions, and myocardiocyte hypertrophy may give rise to atrial structural and functional changes in AF. The efficacy of angiotensinonverting enzyme inhibitors and angiotensin receptor antagonists is justified in patients with left ventricular systolic dysfunction.